Rheology and Rheokinetics of Photosensitive Micelle Composed of 3-Chloro-2-Hydroxypropyl Oleyl Dimethyl Ammonium Acetate and trans-4-Phenylazo Benzoic Acid. Issue 11 (1st November 2016) - Yang, Mo; Fang, Bo; Jin, Hao; Li, Kejing; Yu, Licheng; Jin, Leiping; Chen, Jie; Wang, Liangyuan; Li, Guodong
Abstract : A novel rheological reversible photosensitive micelle composed of 3-chloro-2-hydroxypropyl oleyl dimethyl ammonium acetate (ODAA) and trans -4-phenylazo benzoic acid ( trans- ACA) was investigated. The mixed micelle system under a suitable molar ratio (ODAA:ACA = 1.25:1) shows great viscoelastic property. Before UV irradiation, the ODAA/ACA micelle system exhibits high viscosity and good viscoelasticity. Upon irradiation by UV light (365 nm), ACA undergoes a photoisomerization from its trans to its cis form, causing a change of the molecular structure, which leads to viscosity decreases obviously; thixotropy and viscoelasticity almost disappear. The above changes of rheological properties can be reversible by exposing to visible light. Furthermore, the rheokinetics process of ODAA/ACA micelle system during UV irradiation was studied and rheokinetics equation was established, which can well describe the changing processes of viscosity and viscoelasticity. The viscoelasticity process is divided into two sections to be simulated by rheokinetics equation. In addition, these photosensitive phenomena are repeatable easily and the mechanism can be validated by UV-vis spectra. GRAPHICAL ABSTRACT: